Implikasi Pemahaman Umat Islam di Desa Bandar Khalifah Mengenai Ayat Kursi Terhadap Keyakinan Pengawasan Allah - Alex Martua Nasution; Syahrin Harahap (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Although the Ayat al-Kursi carries profound theological meaning, many Muslims tend to focus primarily on its virtues and practical benefits while paying less attention to its conceptual link with the belief in Allah’s constant supervision. This study aims to explore how Muslims understand Ayat al-Kursi and how such understanding influences their awareness of divine supervision in daily life. Using a qualitative approach through literature review and interviews, the research reveals that while many Muslims appreciate the functional benefits of Ayat al-Kursi, they do not always associate it with moral and ethical dimensions such as self-regulation, honesty, and caution in actions. These findings highlight the need to strengthen a more comprehensive understanding of Ayat al-Kursi so that the value of divine surveillance can be more fully internalized within the spiritual and social behavior of the Muslim community.